Processing of Corn Weevil and Elephant Grass (Pennisetum Purpureum) to Improve the Quality of Cattle Feed Production - R. Anggia Listyaningrum; Rezka Arina Rahma; Ica Purnamasari; Fuad Indra Kusuma (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Cows are one of the farm animals that are very popular with farmers. In the villages many people have cattle in their homes. Likewise with the Wono Asri 3 Farmer Group which also has several members who choose to become cattle breeders. Raising cattle is indeed very profitable, but farmers need to have skills and understanding in order to get these benefits. One of the things that needs to be considered in raising cows is feed. Cattle farmers have various types, including some who like to give forage feed (such as grass, weeds, and corn weevils) only, and some like to mix it with concentrate feed. Forage feed is relatively cheaper, but it requires more effort in providing it, while concentrate feed is easier to provide but the price is more expensive.  This then affects the farmer's expenditure on feed preparations. Therefore, there is a need for new innovations so that farmers can provide feed at a lower price, but it is easy to provide and of course the quality of the products produced. The activities offered from this PkM are mentoring, and training on processing Corn Weevil and elephant grass (pennisetum purpureum) for members of the Wono Asri 3 Farmer Group. This activity aims to equip the knowledge and skills of processing Corn Weevil and elephant grass into quality animal feed. This activity will be carried out using various appropriate implementation methods such as deliberation, brainstorming, interviews, demonstrations and practices. The planned stages of activities are coordination of teams and partners, identification of target group learning needs including farm conditions and corn weevil processing equipment needed, planning activities involving target groups, training, and mentoring.